2015
DOI: 10.1364/boe.6.000933
|View full text |Cite
|
Sign up to set email alerts
|

Optimal wavelength combinations for near-infrared spectroscopic monitoring of changes in brain tissue hemoglobin and cytochrome c oxidase concentrations

Abstract: Abstract:We analyze broadband near-infrared spectroscopic measurements obtained from newborn piglets subjected to hypoxia-ischemia and we aim to identify optimal wavelength combinations for monitoring cerebral tissue chromophores. We implement an optimization routine based on the genetic algorithm to perform a heuristic search for discrete wavelength combinations that can provide accurate concentration information when benchmarked against the gold standard of 121 wavelengths. The results indicate that it is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 39 publications
3
72
0
Order By: Relevance
“…(In this opinion article, we explicitly assume that fNIRS instrumentation can accurately monitor and resolve the concentration changes in [ [HHb] as it has been reported that certain wavelength combinations can result in "crosstalk" between the chromophores. By crosstalk we mean to describe the phenomena that a genuine change in one chromophore concentration is also inducing a spurious measured concentration change in another; for a more detailed discussion of this issue see section "Selection of optimum wavelengths" in the recent review article by Scholkmann et al 4 and the recent study by Arifler et al 5 It is considered good practice for authors to report the wavelengths of their fNIRS instrument used in their study).…”
Section: Changes In Functional Near-infrared Spectroscopy Signals Repmentioning
confidence: 99%
“…(In this opinion article, we explicitly assume that fNIRS instrumentation can accurately monitor and resolve the concentration changes in [ [HHb] as it has been reported that certain wavelength combinations can result in "crosstalk" between the chromophores. By crosstalk we mean to describe the phenomena that a genuine change in one chromophore concentration is also inducing a spurious measured concentration change in another; for a more detailed discussion of this issue see section "Selection of optimum wavelengths" in the recent review article by Scholkmann et al 4 and the recent study by Arifler et al 5 It is considered good practice for authors to report the wavelengths of their fNIRS instrument used in their study).…”
Section: Changes In Functional Near-infrared Spectroscopy Signals Repmentioning
confidence: 99%
“…One strategy to overcome this limitation is to use a series of wavelengths in order to increase signal-to-noise ratio and to decrease cross talk artifacts. 90 In contrast to the two techniques mentioned in Secs. 2.4.1 and 2.4.2, here we use only two wavelengths emanating from coherent sources, which decrease our spectral resolution and accuracy.…”
mentioning
confidence: 98%
“…MC is computationally expensive and thus simulations were carried out at wavelengths 784, 800, 818, 835, 851, 868, 881 and 894 nm chosen according to. 16 Synthetic detectors were defined at 1, 2 and 3 cm (euclidean distance) to measure the exiting light mimicking the experimental setup. The synthetic detectors were 1 mm wide and were assumed to accept incoming photon with the same efficiency from all directions.…”
Section: Simulated Datamentioning
confidence: 99%